Sounds wild and broken : sonic marvels, evolution's creativity, and the crisis of sensory extinction - Haskell, David George (Viking, 2022)
"A rich exploration of how the evolution of both natural and manmade sounds have shaped us and the world, and how the world's acoustic diversity is currently in grave danger of being destroyed. We live on a planet that is wrapped in the diverse acoustic marvels of song and speech. Yet never has this diversity been so threatened as it is now. Braiding his experience as a listener and an ecologist with the latest scientific discoveries, David Haskell explores the acoustic wonders of our planet. Starting in deep time with the origins of animal song and traversing the whole arc of Earth's history, he illuminates and celebrates the creative processes that have produced the varied sounds of our world. From the powers of animal sexuality and environmental change, to the unpredictable, improvisational whims of genetic evolution and cultural change, sounds on Earth are the products of and catalysts for vibrant ecosystems. Four interconnected sensory crises are currently diminishing the vitality of our sonic world. Deforestation is erasing the most complex communities of sounds the world has ever known. In the oceans, machine noise has created a living hell for the most acoustically sensitive animals on the planet. In cities, noise has resulted in dire sonic inequities among people, the result of racism, sexism, and power asymmetries. Last, in forgetting or being barred from hearing the voices of the living Earth, we lose both the experience of joyful connection and the foundation for ethics and action. As wild sounds disappear forever and human noise smothers other voices, the Earth becomes flatter, blander. According to Haskell, this decline is not a mere loss of sensory ornament. Sound is a generative force, and so the erasure of sonic diversity makes the world less creative. His book is an invitation to listen, wonder, belong, and act."--